Public Perceptions of the Communication Strategy of the Surabaya City National Narcotics Agency (BNN) on Instagram - Mahmudah, Luly Alya (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the public's perception of the Surabaya City National Narcotics Agency's (BNNK) communication strategy on Instagram in disseminating drug prevention messages. Against the backdrop of social media's role as an interactive platform, this qualitative study uses a case study method with in-depth interviews with three informants as the main data. The data were analyzed using Stuart Hall's reception analysis theory, which found that the BNNK's communication strategy is effective, as evidenced by the majority of the audience being in a dominant-hegemonic position, receiving messages completely and being driven to perform social actions. However, the presence of a negotiated position in some audience members indicates factors influencing perception differences, such as the expectation for stronger interaction and community building. It is concluded that the effectiveness of BNNK's communication depends on its ability to adapt to become a community facilitator, not just a one-way message broadcaster.